PERTANGGUNGJAWABAN PIDANA DALAM KECELAKAAN LALU LINTAS YANG DILAKUKAN OLEH ANAK DI WILAYAH HUKUM KEPOLISIAN SEKTOR MANDAU - Samuel '; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The rise of traffic accidents that occurred in Mandau not only influenced by the state of the road is not good and the problem of traffic signs, but the main factor of traffic accidents is the human factor itself which often traffic violations. According Act No. 22 of 2009 on Traffic and Transport road Article 115 (b) mentioned '' road motor vehicle drivers are prohibited berbalapan with other motor vehicles '', but the reality on the ground is still very much encountered motorcyclists who drive with High-speed.As for the subject matter in this study are as follows: How is the implementation of the criminal responsibility of traffic accidents committed by children in the jurisdiction of police Saber, How to completion of a crime in a traffic accident committed by a child in the jurisdiction of police Saber, What constraints and efforts in the implementation of criminal responsibility in a traffic accident committed by a child in the jurisdiction of Police Mandau The method used is through sociological research, which uses an empirical approach is an attempt to approach the problems examined with real legal nature or in accordance with the realities of life in society, because in this study the authors directly conduct research on locations or places studied in order to give an overview complete and clear about the issues being investigatedResults of a case study of children in the case of a traffic accident in the jurisdiction of police station saber is passed by way of distinguishing criminal offenses such traffic to the traffic accident to the traffic accident (misdemeanor) and the crime of causing serious injury or death of a person (a criminal offense weight).Keyword : Criminal Responsibility - Children - Traffic Accident